2003
DOI: 10.1073/pnas.0931261100
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of human breast cancer progression

Abstract: Although distinct pathological stages of breast cancer have been described, the molecular differences among these stages are largely unknown. Here, through the combined use of laser capture microdissection and DNA microarrays, we have generated in situ gene expression profiles of the premalignant, preinvasive, and invasive stages of human breast cancer. Our data reveal extensive similarities at the transcriptome level among the distinct stages of progression and suggest that gene expression alterations conferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

66
661
3
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 793 publications
(736 citation statements)
references
References 19 publications
66
661
3
6
Order By: Relevance
“…However, genomic data analyses have revealed that most tumor cell gene expression changes occur at the transition from normal to DCIS, with few additional changes in expression occurring at the transition from DCIS to overt invasive disease. 4,5 These observations implicate key roles for nonepithelial cells in progression to invasive disease. 6,7 The lack of relevant model systems has hindered our understanding of the DCIS to invasive transition.…”
mentioning
confidence: 85%
“…However, genomic data analyses have revealed that most tumor cell gene expression changes occur at the transition from normal to DCIS, with few additional changes in expression occurring at the transition from DCIS to overt invasive disease. 4,5 These observations implicate key roles for nonepithelial cells in progression to invasive disease. 6,7 The lack of relevant model systems has hindered our understanding of the DCIS to invasive transition.…”
mentioning
confidence: 85%
“…Analysis of global gene expression in different types of human cancers compared to the normal tissue from which the cancers originated, has identified many genes that are overexpressed in the cancers (Okutsu et al, 2002;Ma et al, 2003;Sotiriou et al, 2004;Jarzab et al, 2005;Yu et al, 2005;Lee et al, 2006b). The expression profile of genes in different normal human tissues (Lotem et al, 2005) was used to analyse the expression of overexpressed genes in tissues other than the tissue from which the cancer originated (Table 2).…”
Section: Plasticity Of Differentiation In Cancer Stem Cells and Transmentioning
confidence: 99%
“…This conclusion is consistent with various observations, including relative risk, gene expression (by microarrays and serial analysis of gene expression), and genome alterations (by cytogenetic analysis, comparative genomic hybridization measurements of gains and losses, and loss of heterozygosity of microsatellite markers). Some of the most distinct changes in gene expression are observed between normal epithelium and DCIS, and between atypical hyperplasia and DCIS (Porter et al, 2001;Ma et al, 2003). Many of these observations have been reviewed by van Diest (1999), Jeffrey and Pollack (2003), and Reis-Filho and Lakhani (2003).…”
Section: Article In Pressmentioning
confidence: 99%